Предмет: Математика,
автор: Аноним
помогити прошууууу)))))))
Приложения:
Ответы
Автор ответа:
0
А1.
= (2⁴)^(⁵/₄) - (3⁻²)^(⁻¹/₂) + (3³)^(²/₃)=
= 2⁵ - 3¹ + 3² = 32-3+9 =38
Ответ: 38
А2.
а) log₈ (1/16) - log₈ 32 = log₈ (2⁻⁴) - log₈ 2⁵ = log₈ (2⁻⁴ : 2⁵) = log₈ 2⁻⁹=
= -9 log₂³ (2) = -9 * (1/3) log₂ 2 = -3 * 1 = -3
б) lg8+lg125=lg(8*125)=lg1000=lg10³=3lg10=3*1=3
в) 2log₁/₃ 6 - ¹/₂ log₁/₃ 400 + 3log₁/₃ ∛45 = log₁/₃ 6² - log₁/₃ 400^(¹/₂) + log₁/₃ (∛45)³ =
= log₁/₃ 36 - log₁/₃ 20 + log₁/₃ 45 = log₁/₃ (36 : 20*45)= log₁/₃ 81 =
= log₁/₃ 3⁴ = log₁/₃ (1/3)⁻⁴ = -4
A3.
3^(⁵/₈) 3^(⁸/₁₃)
5/8 8/13
65/104 > 64/104
3^(⁵/₈) > 3^(⁸/₁₃)
B1.
⁴√40 * 2^(¹/₄) : 5^(⁻³/₄) = (2³ * 5)^(¹/₄) * 2^(¹/₄) : 5^(-³/₄)=
=2^(³/₄) * 5^(¹/₄) * 2^(¹/₄) : 5^(-³/₄) = 2^(³/₄ ⁺ ¹/₄) * 5^(¹/₄ ⁺ ³/₄)=
= 2¹ * 5¹ = 10
B2.
y=log₀.₃ (3x+4)
3x+4>0
3x>-4
x>-4/3
D(y)=(-4/3; +∞)
y=log₀.₄ (x² -9)
x²-9>0
(x-3)(x+3)>0
x=3 x=-3
+ - +
------ -3 ----------- 3 ------------
х∈(-∞; -3)U(3; +∞)
D(y)=(-∞;-3)U(3; +∞)
С1.
8х+1 = (2x^(¹/₃))³ + 1³ = (2x^(¹/₃)+1)(4x^(²/₃) -2∛x +1) =
4х^(²/₃) -2∛x +1 4x^(²/₃) - 2∛x +1 4x^(²/₃) -2∛x +1
= 2∛x + 1
= (2⁴)^(⁵/₄) - (3⁻²)^(⁻¹/₂) + (3³)^(²/₃)=
= 2⁵ - 3¹ + 3² = 32-3+9 =38
Ответ: 38
А2.
а) log₈ (1/16) - log₈ 32 = log₈ (2⁻⁴) - log₈ 2⁵ = log₈ (2⁻⁴ : 2⁵) = log₈ 2⁻⁹=
= -9 log₂³ (2) = -9 * (1/3) log₂ 2 = -3 * 1 = -3
б) lg8+lg125=lg(8*125)=lg1000=lg10³=3lg10=3*1=3
в) 2log₁/₃ 6 - ¹/₂ log₁/₃ 400 + 3log₁/₃ ∛45 = log₁/₃ 6² - log₁/₃ 400^(¹/₂) + log₁/₃ (∛45)³ =
= log₁/₃ 36 - log₁/₃ 20 + log₁/₃ 45 = log₁/₃ (36 : 20*45)= log₁/₃ 81 =
= log₁/₃ 3⁴ = log₁/₃ (1/3)⁻⁴ = -4
A3.
3^(⁵/₈) 3^(⁸/₁₃)
5/8 8/13
65/104 > 64/104
3^(⁵/₈) > 3^(⁸/₁₃)
B1.
⁴√40 * 2^(¹/₄) : 5^(⁻³/₄) = (2³ * 5)^(¹/₄) * 2^(¹/₄) : 5^(-³/₄)=
=2^(³/₄) * 5^(¹/₄) * 2^(¹/₄) : 5^(-³/₄) = 2^(³/₄ ⁺ ¹/₄) * 5^(¹/₄ ⁺ ³/₄)=
= 2¹ * 5¹ = 10
B2.
y=log₀.₃ (3x+4)
3x+4>0
3x>-4
x>-4/3
D(y)=(-4/3; +∞)
y=log₀.₄ (x² -9)
x²-9>0
(x-3)(x+3)>0
x=3 x=-3
+ - +
------ -3 ----------- 3 ------------
х∈(-∞; -3)U(3; +∞)
D(y)=(-∞;-3)U(3; +∞)
С1.
8х+1 = (2x^(¹/₃))³ + 1³ = (2x^(¹/₃)+1)(4x^(²/₃) -2∛x +1) =
4х^(²/₃) -2∛x +1 4x^(²/₃) - 2∛x +1 4x^(²/₃) -2∛x +1
= 2∛x + 1
Автор ответа:
0
спасибо большое
Похожие вопросы
Предмет: Литература,
автор: daniilemelanov46
Предмет: Українська література,
автор: IntelGraph
Предмет: Математика,
автор: Clouddy
Предмет: Математика,
автор: zareckaya1982
Предмет: Алгебра,
автор: ТалимовТимур